Comparison of Students' Mental Wellbeing, Anxiety, Depression, and Quality of Life During COVID-19's Full and Partial (Smart) Lockdowns: A Follow-Up Study at a 5-Month Interval - Aqeel, Muhammad; Rehna, Tasnim; Shuja, Kanwar Hamza; Abbas, Jaffar (Frontiers in Psychiatry, 2022)
Objective: Scholars have debated the COVID-19's full and partial lockdowns effectivity to control the transmission of the new case. They emphasized the provision of required economic and social resources worldwide. Past literature related to COVID-19 has contributed little evidence to examine the efficacy of full and partial lockdowns measures with experimental perspectives at different intervals. This study bridges this literature gap and explores the full and smart lockdowns' impacts on Pakistani students' mental health, depression, quality of life, and anxiety symptoms, during the various waves of the COVID-19 pandemic. Method: This pre-test and post-test experimental designed web-based survey recruited forty students from March 23 to August 23, 2020, and recorded their responses. The study incorporated four standardized psychological instruments to receive the desired datasets related to students' mental health, quality of life, anxiety, and depression. Researchers shared data links with the participants via social media, WhatsApp. The study applied one-way and multivariate ANOVA tests (analysis of variance) to draw the desired results. Results: This study's findings suggest that both full and partial COVID-19's lockdowns effectively improve students' mental health and quality of life. These measures help reduce anxiety and depressive symptoms among university students. The study results exhibit that partial lockdown (PL) is more effective in improving quality of life. Besides, PL helps reduce anxiety symptoms than complete lockdown among Pakistani students. Conclusion: The present study's findings suggest that students are vulnerable. They need particular interventions and preventive measures to protect and improve their mental health and quality of life during a global pandemic. As the stressful experience of the epidemic persists in Pakistan, it will also be interesting to examine the psychological impact of the successive waves of the COVID-19 pandemic.